The Identification and Elimination of Waste Activities in The Gray Yarn Processing Company - Arifa, Dhinar Elma; Widodo, Imam Djati; Fausa, Erlangga (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to identify the types of waste and recommend improvements to minimize waste that occurs in the gray yarn processing company. Value Stream Mapping (VSM) is used to analyze the flow of materials and information throughout the production process. The main objective is to identify and eliminate waste, thereby improving efficiency and productivity in manufacturing operations. The biggest types of waste in the grey yarn processing production process of the preparation department are Unnecessary motion and Overprocessing waste types at 30% each, Unnecessary Inventory at 20%, and transportation at 20%. The recommendations given can reduce the overall leadtime from 58967 seconds to 58771 seconds.